Characterizing microcycles` workload when combining two days structure within single training sessions during congested fixtures in an elite male soccer team - Gómez-Díaz, A.; Nakamura, F. Y.; Menezes, P.; Barreira, J.; Figueiredo, P.; Coutinho, D. (Biology of Sport, 2024)
This study aimed to describe and compare specific matchdays sessions and playing positions external load during congested fixtures in elite football when combining the objectives from two different training days in one session. Data was collected from 27 players from the 1st Brazilian division (28.7±18.61 years) that participated in the following training days during congested fixtures (n = 16 weeks): a) Match day+1 (MD+1MD-2, session 1 day after the game with tasks from MD+1 and MD-2 sessions, n = 9); b) Matchday-2 (MD-2MD+2, session 2 days prior to subsequent match with tasks from MD-2 and MD+2 sessions, n = 11); c) Matchday-1 (MD-1MD+2, session 1 day prior to subsequent match with tasks from MD-1 and MD+2 sessions, n = 12); and d) Matchday-1 (MD-1MD+3, session 1 day prior to subsequent match with tasks from MD-1 and MD+3 sessions, n = 11). External load was collected with global positioning systems, while internal load with the rating of perceived exertion (RPE). The MD+1MD-2 showed higher total distance covered (F = 116.92, p < 0.001) and player load (F = 56.67, p < 0.001) values than the other three training days, while both the MD+1MD-2 and MD-2MD+2 revealed higher distance covered at high-speed running (F = 22.43, p < 0.001) and high metabolic load distance covered (F = 75.98, p < 0.001) than both MD-1 sessions. Fullbacks covered higher high-speed running distance (F = 3.6, p = 0.033) than center backs, while midfielders reported higher RPE (F = 5.29, p = 0.003) values than defensive midfielders and fullbacks. Coaches may use the MD+1MD-2 to emphasize total distance covered, while both MD+1MD-2 and MD-2MD+2 to promote HSR and HML distance compared to MD-1 sessions. In addition, combining training sessions allows to normalize external load across playing positions with the exception of fullbacks that are exposed to higher stimulus.